Quasinormal Modes of Static Ellis-Bronnikov Wormholes - Azad, Bahareh (Gravity, Cosmology, and Astrophysics, 2023)
Quasinormal modes represent characteristic features of compact objects, since they entail their reaction to perturbations. While black holes and neutron stars in general relativity have been extensively studied and their quasinormal modes are well-known, the complete set of quasinormal modes for wormholes was only recently obtained. Here we discuss how to determine these quasinormal modes of Ellis-Bronnikov wormholes. These wormholes are static spherically symmetric solutions of general relativity coupled to a phantom scalar field. We obtain the axial and polar quasinormal modes and show, that for the massless wormhole a threefold degeneracy of the modes arises, i.e., there is isospectrality of the modes.